Expression of CTLA-4 and Foxp3 in peripheral blood T cells of patients with squamous cell laryngeal carcinoma - Starska, Katarzyna; Forma, Ewa; Lewy-Trenda, Iwona; Woś, Jan; Papież, Paweł; Mochocki, Marcin; Morawski, Piotr; Kopta, Renata; Bryś, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2013)
Cytotoxic T lymphocyte-associated antigen 4 (CTLA-4, CD152) and Foxp3 (forkhead box P3) are receptors present on T cells which play a critical role in the down-regulation of antigen-activated immune responses. To evaluate the potential influences of CTLA-4 and Foxp3 on cancer invasiveness, a case-control study was conducted in 86 patients treated for squamous cell laryngeal carcinoma. The abundance of CTLA-4 and Foxp3 gene transcripts in the purified peripheral blood mononuclear cells (PBMCs) by quantitative real-time PCR (qRT-PCR) was determined. The analysis of proteins by Western blot was performed. The relationships between CTLA-4 and Foxp3 gene and protein expression as well as the aggressiveness of tumor determined on pT, type and depth of invasion were investigated. Our work revealed a significant dependence of mRNA CTLA-4 on tumor front grading (TFG) total score (p = 0.04) as well as CTLA-4 protein expression on pT (p = = 0.03) and type of invasion (p = 0.03). Advanced pT3-pT4 tumors with diffuse infiltration and > 14 TFG points were characterized by higher average values of CTLA-4 protein in PBMCs. Our data also demonstrated significant differences between Foxp3 protein levels in relation to pT (p = 0.04), depth of invasion (p = = 0.02) and type of invasion (p = 0.03). In tumors with the highest invasiveness identified by the pT3-pT4 status, deep invasion with involvement of cartilage and diffuse infiltration, the highest Foxp3 protein level was observed. In conclusion, these results suggest an impact of CTLA-4 and Foxp3 in determining proliferative and aggressive potential of laryngeal carcinoma, highlighting the significance of CTLA-4 and Foxp3 as potential predictive indicators.